Discrimination Is Associated with Elevated Cardiovascular Disease Risk among African Immigrants in the African Immigrant Health Study - Turkson-Ocran, Ruth-Alma N. (Ethn Dis, 2020)
BACKGROUND: African Americans and other persons of African descent in the United States are disproportionately affected by cardiovascular diseases (CVD). Discrimination is associated with higher CVD risk among US adults; however, this relationship is unknown among African immigrants. METHODS: The African Immigrant Health Study was a cross-sectional study of African immigrants in Baltimore-Washington, DC, with recruitment and data collection taking place between June 2017 and April 2019. The main outcome was elevated CVD risk, the presence of ≥3 CVD risk factors including hypertension, diabetes, high cholesterol, overweight/obesity, tobacco use, and poor diet. The secondary outcomes were these six individual CVD risk factors. The exposure was discrimination measured with the Everyday Discrimination Scale; summed scores ≥2 on each item indicated frequent experiences of discrimination. Resilience was assessed with the 10-item Connor-Davidson resilience scale. Logistic regression was used to examine the odds of elevated CVD risk, adjusting for relevant covariates. RESULTS: We included 342 participants; 61% were females. The mean (±SD) age was 47(±11) years, 61% had at least a bachelor’s degree, 18% had an income <$40,000, and 49% had lived in the US ≥15 years. Persons with frequent experiences of discrimination were 1.82 times (95%CI: 1.04–3.21) more likely to have elevated CVD risk than those with fewer experiences. Resilience did not moderate the relationship between CVD risk and discrimination. CONCLUSION: African immigrants with frequent experiences of discrimination were more likely to have elevated CVD risk. Targeted and culturally appropriate interventions are needed to reduce the high burden of CVD risk in this population. Health care providers should be aware of discrimination as a meaningful social determinant of CVD risk. At the societal level, policies and laws are needed to reduce the occurrence of discrimination among African immigrants and racial/ethnic minorities.